Obstacling Factors in Entrepreneurship in Songket Craftmen - Ikhsan Dani Nugraha; Muhammad Giatman; Yuliana (Institute of Computer Science (IOCS), 2022)
This study aims to see the factors that hinder the entrepreneurship of songket craftsmen in Agam district, West Sumatra, the research method used in this study uses the confirmatory factor analysis research method. Using descriptive analysis, the data taken through the questionnaire is then presented in graphic form. The results of the research obtained are Internal factors that hinder entrepreneurial embroidery craftsmen are duties as a housewife, pregnancy period and the task of taking care of children. While from an emotional point of view, it is difficult to make decisions because there are too many considerations. In addition, the condition of feelings and relationships between men and women in an effort interferes with their concentration in doing business. For external factors, socio-cultural factors that hinder female craftsmen in Jorong Lundang in entrepreneurship are the assumptions of society that those who make a living are women.